Faktor-Faktor yang Mempengaruhi Kepuasan Pelanggan pada Transportasi Online Roda Dua PT X - Istiana, Dipa Mulia (Jurnal Manajemen, 2021)
The industrial revolution 4.0 changes the direction of human activity from conventional to digital, almost all aspects of life. as happened in the world of transportation, where the digital era presents transportation that can be ordered through our gedget. The purpose of this study was to determine, analyze and examine the relationship between the influence of service quality, security, price perception, payment methods and efficiency on customer satisfaction. This type of research is conclusive, namely finding evidence of a causal relationship (causal relationship) between variables. The number of indicators in this study were 24 indicators, so the number of samples to be taken for this study were 264 respondents. The results of the analysis state that the Efficiency variable has a significant positive effect on the Customer Satisfaction variables. While the variables of security, service quality, and perceived price have a positive effect on customer satisfaction but not significant, while the payment method variable has a positive and significant effect on customer satisfaction. Service quality does not have a significant effect on customer satisfaction, the security variable does not significantly influence customer satisfaction.